Invasive species and biotic homogenization in temperate aquatic plant communities. Issue 4 (3rd February 2020) - Muthukrishnan, Ranjan; Larkin, Daniel J.
Abstract: Aim: Biotic homogenization (BH), a reduction in the distinctness of species composition between geographically separated ecological communities in a region, is an important but underappreciated potential consequence of biological invasions. While BH theory has always considered invasions, it has generally been in a relatively narrow context that the cosmopolitan nature of invasive species increases BH because of their shared presence across many locations. We sought to evaluate this component of BH as well as broader effects of invasive species on BH through changes in native communities, including overall reductions in species richness or shifts in species composition. Location: Minnesota, USA. Time period: 2002–2014. Major taxa studied: Aquatic macrophytes, including both vascular plants and attached macroalgae. Methods: We used surveys of aquatic macrophyte communities from 1, 102 shallow lakes in Minnesota, USA (including 248 lakes with repeated surveys) to evaluate relationships between invasion, native species and BH. Results: We found that the presence of invasive species was associated with BH and that this pattern was reflected in both the total community (i.e., with invasive species included) and in the composition of the native species community alone. We found that invaded lakes were more compositionally similar to each other than uninvaded lakes, but that both groups were becoming more similar over time—despite neither group exhibiting declines in species richness. This pattern was largely driven by shifts in the native community itself, with common species becoming more widespread and rare species becoming rarer. Main conclusions: Invasive species increase measures of community similarity through their own presence in multiple locations, and also by influencing the composition of native species. These patterns have important implications for conservation and management and suggest that BH should be considered more widely in evaluating the impacts of biological invasions and developing response strategies.